If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -2.8 = x Combine like terms: 7 + -2.8 = 4.2 4.2 = x Solving 4.2 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4.2 + -1x = x + -1x Combine like terms: x + -1x = 0 4.2 + -1x = 0 Add '-4.2' to each side of the equation. 4.2 + -4.2 + -1x = 0 + -4.2 Combine like terms: 4.2 + -4.2 = 0.0 0.0 + -1x = 0 + -4.2 -1x = 0 + -4.2 Combine like terms: 0 + -4.2 = -4.2 -1x = -4.2 Divide each side by '-1'. x = 4.2 Simplifying x = 4.2
| 12-[4-2(y+1)]*2=2y+6 | | 1.8-(-3.7)=x | | -2x-41=-5(x+4) | | (6x-32)+(2x-20)=180 | | 10x-19=4x+1 | | 5.8+(-2.5)=x | | 12-[4-2(y+1)]=2y+6 | | 6-3.98=x | | (y-12)+(3y-8)=180 | | 28a^2-192a-28=0 | | 7w-5=3w+11 | | 9x+29=93-5x | | 10-(-10)-7-5=x | | 8.5x-3.5x=-94 | | (-11)-8+1-(-6)=x | | 4x+2=x-11 | | (-3)+5+(-5)+12=x | | x/2+3=1/2 | | 6+(-7)+(-5)-(-2)=x | | 6y=45-3y | | 7+(-1)+12-7=x | | (-11)-(-14)+7=x | | 9+6(2)7n= | | 0.5x-1.4=1.1 | | (-7)-(-2)-9=x | | -6-1=-32y+32 | | 16-(-13)-(-5)=x | | 6(y-4)=5[17-3(2y-13)] | | 4-5+7k=33 | | -9-200x+(0.015)(100)= | | (-16)-6+(-5)=x | | 12+0.4(x-2)=10 |